2011
DOI: 10.1093/nar/gkr443
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the relationships between DNaseI HS, histone modifications and gene expression reveals distinct modes of chromatin domains

Abstract: To understand the molecular mechanisms that underlie global transcriptional regulation, it is essential to first identify all the transcriptional regulatory elements in the human genome. The advent of next-generation sequencing has provided a powerful platform for genome-wide analysis of different species and specific cell types; when combined with traditional techniques to identify regions of open chromatin [DNaseI hypersensitivity (DHS)] or specific binding locations of transcription factors [chromatin immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 66 publications
(84 reference statements)
6
48
0
1
Order By: Relevance
“…For example, in Arabidopsis, genes with expression patterns that are altered in response to dehydration show a pattern of H3K4me3 at transcriptional start sites similar to the one that we observe for down-regulated HD genes, and this pattern persists in both the dehydrated and watered state (26). The H3K4me3 classes that we observe also closely resemble the clusters previously reported for H3K4me2 in human CD4+ T cells (27). In this case, genes with tissue-specific expression showed a broader distribution of the mark extending into the expressed portion of the gene, suggesting that a unique chromatin signature at specific promoters may regulate their tissue-specific expression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, in Arabidopsis, genes with expression patterns that are altered in response to dehydration show a pattern of H3K4me3 at transcriptional start sites similar to the one that we observe for down-regulated HD genes, and this pattern persists in both the dehydrated and watered state (26). The H3K4me3 classes that we observe also closely resemble the clusters previously reported for H3K4me2 in human CD4+ T cells (27). In this case, genes with tissue-specific expression showed a broader distribution of the mark extending into the expressed portion of the gene, suggesting that a unique chromatin signature at specific promoters may regulate their tissue-specific expression.…”
Section: Discussionsupporting
confidence: 87%
“…We used sequence analysis to identify potential transcriptional regulators that could be recruiting methyltransferases and demethylases to differentially expressed genes in R6/2 mice. Previous studies (24,27) have shown that the sites of such regulators should not be expected directly underneath the peaks of methylation. Therefore, we determined the location of chromatin accessible binding sites for regulatory proteins near the enriched H3K4me3 regions in WT and R6/2 mice based on an empirical spatial distribution derived from DNase-Seq and H3K4me3 ChIP-Seq data (Fig.…”
Section: H3k4 Trimethylation Changes At the Dysregulated Promoters In Hdmentioning
confidence: 97%
“…5A). 24,25 This is confirmed with a comparison of peak tracks of H3K4me3 and H3K27me3 in H1 cells data sets (GSE25070 and GSE21815) were mined. 5,27 The first data set consists of transcript levels of 26 CRC and 26 matched normal colon tissues obtained with Illumina beadchips.…”
Section: Dna Methylation Profiles Of Crc Cases and Matched Controlssupporting
confidence: 58%
“…Almost all of the DHS regions fell within introns (46%) or intergenic regions (45%) (Supplemental Fig. S1B), similar to the genome-wide distribution of DHS regions in other cell types (Shu et al 2011). A small number of DHSs (156/4000 or 4%) were "promoter-proximal," i.e., falling within −1 kb to +100 bp relative to the nearest TSS (Supplemental Fig.…”
Section: Identification and Characterization Of Candidate Cre Regionssupporting
confidence: 56%